Sensitivity of phytoplankton, zooplankton and macroinvertebrates to hydrogen peroxide treatments of cyanobacterial blooms. (15th October 2022) - Weenink, Erik F.J.; Kraak, Michiel H.S.; van Teulingen, Corné; Kuijt, Senna; van Herk, Maria J.; Sigon, Corrien A.M.; Piel, Tim; Sandrini, Giovanni; Leon-Grooters, Mariël; de Baat, Milo L.; Huisman, Jef; Visser, Petra M.
Highlights: H2 O2 toxicity tests were run with 26 phytoplankton, zooplankton and macrofauna taxa. A species sensitivity distribution was used to predict H2 O2 effects on lake biota. Taxa predicted to be at risk were indeed affected by H2 O2 treatments of lakes. Higher H2 O2 concentrations suppressed cyanobacteria but also affected rotifers. This dose-dependent trade-off may influence the decision to treat a lake. Abstract: Addition of hydrogen peroxide (H2 O2 ) is a promising method to acutely suppress cyanobacterial blooms in lakes. However, a reliable H2 O2 risk assessment to identify potential effects on non-target species is currently hampered by a lack of appropriate ecotoxicity data. The aim of the present study was therefore to quantify the responses of a wide diversity of freshwater phytoplankton, zooplankton and macroinvertebrates to H2 O2 treatments of cyanobacterial blooms. To this end, we applied a multifaceted approach. First, we investigated the 24-h toxicity of H2 O2 to three cyanobacteria ( Planktothrix agardhii, Microcystis aeruginosa, Anabaena sp.) and 23 non-target species (six green algae, eight zooplankton and nine macroinvertebrate taxa), using EC50 values based on photosynthetic yield for phytoplankton and LC50 values based on mortality for the other organisms. The most sensitive species included all three cyanobacterial taxa, but also the rotifer Brachionus calyciflores and the cladocerans Ceriodaphnia dubia and Daphnia pulex . Next, the EC50 and LC50 values obtained from the laboratory toxicity tests were used to construct a species sensitivity distribution (SSD) for H2 O2 . Finally, the species predicted to be at risk by the SSD were compared with the responses of phytoplankton, zooplankton and macroinvertebrates to two whole-lake treatments with H2 O2 . The predictions of the laboratory-based SSD matched well with the responses of the different taxa to H2 O2 in the lake. The first lake treatment, with a relatively low H2 O2 concentration and short residence time, successfully suppressed cyanobacteria without major effects on non-target species. The second lake treatment had a higher H2 O2 concentration with a longer residence time, which resulted in partial suppression of cyanobacteria, but also in a major collapse of rotifers and decreased abundance of small cladocerans. Our results thus revealed a trade-off between the successful suppression of cyanobacteria at the expense of adverse effects on part of the zooplankton community. This delicate balance strongly depends on the applied H2 O2 dosage and may affect the decision whether to treat a lake or not. Graphical abstract: Image, graphical abstract